Effectiveness of Self-Management Training, “EDUDARA”, on Psychological Wellbeing and Cortisol Levels in Breast Cancer Patients during the COVID-19 Pandemic - Supriati, Lilik; Nova, Renny; Rodli, Muhammad; Ahsan, Ahsan; Hidaayah, Nur; Rismayanti, I Dewa Ayu (Nurse Media Journal of Nursing, 2024)
Background: Women diagnosed with breast cancer often experience emotional distress, leading to a decrease in psychological well-being. Online self-management training during the COVID-19 pandemic is crucial for maintaining psychological well-being, as it is closely related to stress hormone cortisol levels, which play a vital role in boosting the body’s immune system. However, research on self-management strategies for breast cancer patients, particularly regarding psychological aspect and its relationship to cortisol levels during the COVID-19 pandemic, remains limited.Purpose: The purpose of this study was to measure the effectiveness of self-management training on psychological well-being and salivary cortisol levels in breast cancer patients.Methods: This study used a pre-post-test quasi-experimental design with a control group. The participants included 70 breast cancer patients undergoing chemotherapy at a hospital in Malang City, East Java, Indonesia, recruited using simple random sampling. Self-management training using the EDUDARA (Edukasi Kanker Payudara) was administered to the participants in the intervention group for six weeks. Data on wellbeing were collected using the Ryff Psychological Wellbeing Questionnaire, while salivary cortisol levels were measured with the DBD cortisol kit using the competitive ELISA method. SPSS with t-tests was used to analyze the data.Results: The average post-test psychological well-being score in the intervention group was 90.3, while in the control group, it was 82.69. The results of statistical tests showed a significant difference in psychological well-being between the two groups, with the intervention group showing greater improvement after the training. Additionally, the mean salivary cortisol level post-training was 4.531 in the intervention group and 6.169 in the control group (p=0.001). This indicates a greater reduction in cortisol levels in the intervention group after training, showing that participants’ psychological condition following the “EDUDARA” training was better than that of the control group.Conclusion: Self-management training had a positive effect on increasing psychological well-being and decreasing salivary cortisol levels among breast cancer patients. Therefore, structured self-management training for these patients can be used for nursing intervention